Sumerian Character Extraction by Using Discrete Wavelet Transform and Split Region Methods - Talib, Moahaimen; S, Jamila Harbi (Kurdistan Journal of Applied Research, 2017)
this paper proposed a new method to extract characters from Sumerian Texts in Sumerian cuneiform tablets from the Ur III period. The work was confronted by the challenges posed by the fact that Sumerian is not a well understood language and it is not similar to any other ancient or modern language, so we offered a new method for extracting characters from Sumerian tablets,it has an accurate results and better time consuming than other methods, taking many tablet images and applying preprocessing methods to enhance and segment the image and then discrete wavelet transformation and we extract characters for each tablet image by split region algorithm, this work will be very helpful to Cuneiforms and scholars in their field.